Investigation of atom arrangement and defects evolution in Ni–Co alloy atomic-precision electrochemical 3D printing using molecular dynamics - Honggang Zhang; Kai Chen; Haibin Liu (Materials & Design)
Electrochemical 3D printing deposition, is becoming a key technology for fabricating metallic structure at the nanoscale. However, precise deposition of Ni–Co alloys faces numerous challenges, regarding the effects of physicochemical reactions on atomic structure, material deposition control, and interfacial phenomena. To gain an in-depth understanding of the microscopic mechanisms in Ni–Co atomic electrodeposition, this study proposes an electric double layer-controlled electrochemical kinetics model and employs molecular dynamics simulations to investigate the effects of direct current (DC) and pulsed current (PC) on Ni–Co atomic electrodeposition. The results reveal that increasing Co improves electrochemical properties and promotes more ordered morphology, thereby optimizing atomic arrangement and reducing deposit defects. Controlling DC current density is critical for forming better crystal structures and enhancing atomic stability. Compared to DC electrodeposition, PC electrodeposition further improves deposit performance by reducing crystal distortion and enhancing the surface integrity of deposits, especially for low pulse duty cycles and high pulse frequency. This study provides significant insights into atomic behavior, deposition mechanisms, and interfacial reactions during electrochemical deposition. It offers essential theoretical support for the effective regulation of the microstructure and surface characteristics of Ni–Co atomic electrodeposition by precisely controlling the formation of perfect crystal structures at the atomic scale.